2023
DOI: 10.25082/amler.2023.01.017
|View full text |Cite
|
Sign up to set email alerts
|

MOOCs 2012-2022: An overview

Abstract: Online learning has proven its effectiveness recently, especially during the coronavirus outbreak [COVID-19] that forced the closure of educational institutions in most countries. Many see MOOCs as an alternative to the traditional education system due to the flexibility of learning time and the absence of economic and geographical constraints. People can access educational content for free through platforms that deliver online learning content. However, MOOCs have long-standing challenges that need to be addr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…Nonetheless, there are main obstacles when using ICT-based learning media, such as inadequate devices, Figure 1 The advantages of the emerging e-pocket book in physics learning lack of digital technology, and a less stable internet network (Asiimwe et al, 2017;Lavidas et al, 2022;Lawrence & Tar, 2018;Ngao et al, 2022;Warioba et al, 2022). Furthermore, the learning model should be student-oriented so the students can seek their knowledge through the used learning media (Papadakis, 2023). Therefore, both teachers and students must be capable of using information technology so that the learning process can run well.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, there are main obstacles when using ICT-based learning media, such as inadequate devices, Figure 1 The advantages of the emerging e-pocket book in physics learning lack of digital technology, and a less stable internet network (Asiimwe et al, 2017;Lavidas et al, 2022;Lawrence & Tar, 2018;Ngao et al, 2022;Warioba et al, 2022). Furthermore, the learning model should be student-oriented so the students can seek their knowledge through the used learning media (Papadakis, 2023). Therefore, both teachers and students must be capable of using information technology so that the learning process can run well.…”
Section: Discussionmentioning
confidence: 99%
“…The main detail to consider about learning algorithms is that they are like a basis for learning computer science and programming because they teach logical thinking and follow a sequence of tasks or activities to achieve a goal or result (Louka, 2022;Papadakis, 2021). With the educational level that Peru manages, a large part of the student body has many learning difficulties (Papadakis, 2023). There are very few national schools that can provide good quality teaching.…”
Section: Literature Reviewmentioning
confidence: 99%
“…M-learning enhances students' field trips and field work experiences through increased interaction, collaboration, and engagement [13]. It facilitates anytime and anywhere access to high quality educational content [14]. Further, it allows the learners to convert their dead time while in transit to productive activity.…”
Section: Mobile Learningmentioning
confidence: 99%
“…However, the flexibility of learning anytime and anywhere may lead to interaction and information overload [15]. Moreover, the benefits of m-learning are based on learner's motivation [14]. A meta-analysis of m-learning studies indicated that most studies focus on system design and effectiveness [16].…”
Section: Mobile Learningmentioning
confidence: 99%